The Intake of Junk Food as an Etiological Factor of Megaloblastic Anemia in Patients visiting Mayo Hospital, Lahore - Zunairah Mughal, Dr; Hira Babar; Raana Akhtar, Dr; Ambareen Hamid, Dr; Sobia Ashraf, Dr; Samina Qamar, Dr (University of Lahore, 2023)
Objective: The study was performed to determine role of junk food intake in the development of megaloblastic anemia. Methodology: It was a clinical based cross-sectional study conducted at Mayo Hospital Lahore in collaboration with Pathology Department of King Edward Medical University from June 2017 to June 2021. All the patients of age 7 to 70 years including males and non-pregnant females attending the Out Patient Department or admitted in the hospital and having hemoglobin values<12 gm/l, MCV more than 95 fl and bone marrow examination suggestive of a megaloblastic change in the marrow (WHO criteria)were included in our study. The patients who had received blood transfusion or hematinic in less than 6 months before diagnosis and pregnant females were excluded from our study. A total 1333 patients were screened, out of which only 160 patients were diagnosed with megaloblastic anemia who had undergone bone marrow trephine biopsy. Their dietary history was taken in detail and history of depression was noted on validated questionnaires. The obtained data was analyzed on the basis of age groups (7-25 years, 26-50 years, 51-75 years) using SPSS descriptive analysis and results were formulated. Results: The study revealed that 160 (12%) of total 1333 patients were diagnosed with megaloblastic anemia on bone marrow trephine biopsy with male to female ratio of 1:1.28. Total 58 (36%) patients belonged to 1-25 years age group 68 (43%) patients to 26-50 years age group and 34 (21%) patients belonged to 51-75 years age group. Junk food consumption was seen (60.3%) in 7-25 years age group as a prevalent etiological factor. Conclusion: Junk food consumption is the major cause of megaloblastic anemia in young population and poor diet in middle age group, whereas comorbidities are the major etiological factor in older people.